Spatial Decision Support System Untuk Pencegahan Kebakaran Hutan (Studi Kasus: Kabupaten Kubu Raya) - Elysa, Made Liya (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2014)
Forest is a natural resource with hugepotential to be utilized for national development.However threats and disturbances on forests andland that is hindering conservation efforts are verycommon. One form of the disorder and the threat isforest fires. Causes of forest fires in WestKalimantan are intentional, fire causes burning andindirect influence. Intentional reason thatconducted on sufficient consideration, for exampleto the traditional land clearance, but due touncontrolled fires spread to other areas.Management activities and geographical mappingare useful as a way of prevention must be plannedand carried out continuously to help decisionmakers in determining the priority areas that areprone to forest fires. This research aims to map theexisting fire-prone areas in Kubu Raya district andanalyze the indicators that have been determinedare hotspots, rainfall, peat thickness, fire-proneareas and residential distance, so it can produce apriority of districts in the determining forest fireproneareas. Analysis of composite prioritization isdone by using Principal Component Analysis (PCA)and analysis of clusters to reduce the decisiveindicator priorities and group the results of thePCA analysis so it can determine the priority ofeach district. The system can manage spatial dataand indicators tabular data and displayed in theform of maps and tables to generate reports andgraphs of forest fire-prone areas. Based on the testresults show an average accreditation formsresponders need to respond to the application bythe percentage of 48,2%